Cadmium-induced changes in haemato-immunological, oxidative stress and antioxidant parameters of Cyprinus carpio: Protective role of curcumin - Pala, Aysegul; Eroglu, Mucahit; Yonar, Serpil Mise; Ispir, Unal; Yonar, Muhammet Enis (Wiley, 2026)
This study examined the adverse effects of sublethal concentrations of cadmium (Cd) and the potential of curcumin (CUR) to mitigate Cd-induced toxicity. We administered 1.5 and 3 mg/L of Cd and 100 mg/kg of CUR to fish (Cyprinus carpio) separately and in combination over 14 days. At the end of the experiments, various haematological and immunological parameters, oxidative stress levels and antioxidant parameters of fish were measured, and the differences between the groups were evaluated. Simultaneous CUR treatment with Cd reversed the changes in haematological parameters in fish, increased immune responses, reduced oxidative stress and normalized the impaired antioxidant enzyme activities. In summary, our study showed that dietary supplementation with CUR may be an effective strategy to reduce the toxic effects of Cd in carp.
Keywords: cadmium; curcumin; haematology; heavy metal; immunity; oxidative stress